Malaria epidemic early warning and detection in African highlands. - Abeku, T; Hay, S; Ochola, S; Langi, P; Beard, B; de Vlas, S; Cox, J (2004)
Malaria epidemics have long been known to recur in the African highlands. Efforts to develop systems of early warning and detection for epidemics are outlined here with special emphasis on the Highland Malaria Project (HIMAL). This project has been conducting research on the operational implementation of a district-based surveillance and epidemic-monitoring system using a network of sentinel sites in four pilot districts of Kenya and Uganda. The potential use of weather monitoring as well as disease surveillance for effective early warning is being investigated.